2022
DOI: 10.2147/dddt.s339305
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label, Phase I, Pharmacokinetic Studies in Healthy Chinese Subjects to Evaluate the Bioequivalence and Food Effect of a Novel Formulation of Abiraterone Acetate Tablets

Abstract: Abiraterone acetate tablets (I)(N-AbA) is a novel tablet co-formulated with the absorption enhancer sodium N-(8-[2-hydroxybenzoyl] amino) caprylate (SNAC). This study aimed to compare the pharmacokinetics, bioequivalence, safety, and food effects of N-AbA with the reference ZYTIGA ® (R-AbA) in healthy Chinese male subjects. Patients and Methods: This study was conducted in three parts. Part I was an open, doseescalation trial conducted in 16 Chinese healthy males; Part II was a randomized, open-label, 2 × 4 cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…Such discrepancy in the fold change for systemic exposure might be due to the different ethnicity and distinct food composition. The magnitude of the food effect in our study was in good agreement with a previous study carried out in Chinese volunteers 27 . As is known, dietary fat could increase the level of endogenous bile salt in the gut, improve the dissolution rate of ABI as a lipophilic drug and therefore result in superior intestinal absorption 31 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such discrepancy in the fold change for systemic exposure might be due to the different ethnicity and distinct food composition. The magnitude of the food effect in our study was in good agreement with a previous study carried out in Chinese volunteers 27 . As is known, dietary fat could increase the level of endogenous bile salt in the gut, improve the dissolution rate of ABI as a lipophilic drug and therefore result in superior intestinal absorption 31 .…”
Section: Discussionsupporting
confidence: 91%
“…5,6 In line with previous studies, prandial status showed extensive effects on the PK of ABI in a Chinese population. It was also reported that fed condition increased C max of ABI in multiple races by 2.2 to 16.8-fold and AUC by 2.0 to 9.7-fold relative to those in fasted condition, [21][22][23][24][25][26][27][28][29][30] respectively. Such discrepancy in the fold change for systemic exposure might be due to the different ethnicity and distinct food composition.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation